ANALISIS SKRINING FITOKIMIA, KADAR TOTAL FENOL-FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT KAYU TANAMAN GALAM RAWA GAMBUT (Melaleuca cajuputi roxb) - Raden Roro Ariessanty Alicia Kusuma Wardhani; Okviyoandra Akhyar; Emilda Prasiska (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Forest galam is forest typical south kalimantan capable of growing on land peat and have the potential as herbs. Bark galam is part plant which remains underutilized. Hence the study was done to know compound bioaktif which is found in bark galam so bark galam could be more used especially as herbs. Screening phytochemistry analysis, the total fenol-flavonoid and the antioxidant activity performed on extract ethanol bark galam. Based on the results of phytochemical screening, compounds of secondary metabolite contained in the bark extract were alkaloid, polyphenol, flavonoid and quinone. Total phenolic was defined by using Folin-Ciocalteu method at wavelengths 748 nm and the results was 33,8646 ppm with the total of phenol level was 30,47814 mg GAE/g of extract. The total flavonoid was specified by using the method of AlCl3 at 373,6 nm. The results showed that the total concentration of flavonoid 0,0942 ppm with the total level of extract flavonoid was 0,2826 mg QE/g of extract. The antioxidant activity test uses DPPH (1,1-diphenyl-2- picrylhidrazyl) method and the measurement uses spectrophotometry UV-Vis at wavelengths 518,90 nm. The comparison compound used is ascorbic acid. Antioxidant activity test showed that the IC50 values in the bark extract is 44,4888 ppm. Antioxidant intensity in the bark of galam extract is included in very strong intensity (<50 ppm).